Immunohistochemical expression of PARP-1 in triple-negative endometrial cancer – a comparison of different score systems - Bulsa, Michał; Jankowska-Szabłowska, Sylwia Romana; Urasińska, Elżbieta (Polish Journal of Pathology, 2022)
Endometrial cancer is the most common malignant neoplasm of the female reproductive system. The number of diagnosed cases is increasing every year. In recent years, the triple-negative phenomenon (TNP) has been identified as one of the determinants of shorter survival in endometrial cancer patients. The aim of the study was to compare the PARP-1 protein expression in triple-negative (TNEC) and non-triple-negative (NTNEC) endometrial cancer patients and determine the relationship between the PARP-1 protein expression in endometrial cancer cells and patient’s overall survival depending on the adopted scale (H-SCORE < 75, H-SCORE < 50, Allred scale). The study involved 265 patients with histopathologically confirmed endometrial cancer. The patients were divided into 2 groups: patients with TNEC and patients with NTNEC. The study was conducted using a tissue microarray technique. Expression of PARP-1 protein was determined by immunohistochemistry. Protein expression evaluation was performed using virtual microscopy and the Image Scope computer image analysis system. The following conclusions were reached: total and individual levels of nuclear or cytoplasmic PARP-1 expression varied with the presence or absence of TNP, and PARP-1 nuclear expression at the 2+ level had a significant effect on the increased risk of death (according to H-SCORE < 75).